2007
DOI: 10.1007/bf02898033
|View full text |Cite
|
Sign up to set email alerts
|

Urinary bisphenol-A concentration in infertile Japanese women and its association with endometriosis: A cross-sectional study

Abstract: Objectives: Bisphenol A (BPA), a raw material commonly used in the manufacture of resins such as polycarbonate and epoxy, is a possible xenoestrogen that is hypothesized to disrupt the human endocrine system. Humans are widely exposed to BPA. We investigated the urinary concentration of BPA in infertile Japanese women and its possible association with endometriosis.Materials and Methods: We recruited 166 women (aged 20-45) who had complained of infertility and visited a university hospital in Tokyo. The subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
3
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 24 publications
0
35
3
1
Order By: Relevance
“…Further, in animal reproduction studies, effects on F1 and F2 generations have also been seen, such as reproductive system effects and behavioral Environ Health Prev Med (2008) 13:332-337 333 abnormalities in animal experiments using mice and rats [8,9,11,21,22]. Moreover, human epidemiological studies have suggested the possibility of an association with a variety of disorders, including effects on the reproductive system, such as hypospadia, undescended testes, and endometriosis [15,19,23,24]; neural development and behavior [12,25]; sex hormones [12,24]; and allergic conditions [26]. In terms of the risk of BPA to infants and children, an expert panel at the Center for the Evaluation of Risks to Human Reproduction of the National Toxicology Program in the United States recently expressed ''some concern that exposure to Bisphenol A causes neural and behavioral effects'' and ''minimal concern that exposure to Bisphenol A potentially causes accelerations in puberty'' [27].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Further, in animal reproduction studies, effects on F1 and F2 generations have also been seen, such as reproductive system effects and behavioral Environ Health Prev Med (2008) 13:332-337 333 abnormalities in animal experiments using mice and rats [8,9,11,21,22]. Moreover, human epidemiological studies have suggested the possibility of an association with a variety of disorders, including effects on the reproductive system, such as hypospadia, undescended testes, and endometriosis [15,19,23,24]; neural development and behavior [12,25]; sex hormones [12,24]; and allergic conditions [26]. In terms of the risk of BPA to infants and children, an expert panel at the Center for the Evaluation of Risks to Human Reproduction of the National Toxicology Program in the United States recently expressed ''some concern that exposure to Bisphenol A causes neural and behavioral effects'' and ''minimal concern that exposure to Bisphenol A potentially causes accelerations in puberty'' [27].…”
Section: Discussionmentioning
confidence: 99%
“…Determination of urinary BPA levels was done using LC-MS/MS [19] on account of its highly reliable identification.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Only a few studies investigating the association between BPA exposure and reproductive/developmental disorders in human subjects have been published since 2007 (Itoh et al, 2007;Padmanabhan et al, 2008;Wolff et al, 2008;Braun et al, 2009;Cobellis et al, 2009;Yang et al, 2009;Li et al, 2010a, b;Meeker et al, 2010;Mendiola et al, 2010;MokLin et al, 2010). Itoh et al (2007) reported no association between urinary BPA concentrations and endometriosis in a cross-sectional study of 140 infertile Japanese women.…”
Section: Other Human Studiesmentioning
confidence: 99%